Analisis Ukuran Mata Pancing Terhadap Hasil Tangkapan Ikan Demersal pada Rawai Dasar (Bottom Longline) di Perairan Pulau Aceh - Syahrul Rivana; Heri Triyono; Maman Hermawan; Abdul Qadir Jailani (Jurnal Perikanan Unram, 2024)
Demersal fish have an important role in the fishing industry in Indonesia due to their high economic value and important role in aquatic ecosystems. Bottom longline gear is a very effective fishing gear for catching demersal fish. The purpose of this study was to examine the effect of different fishing line sizes on demersal fish catches. This research was conducted from November 2023 to December 2023 in the waters of Aceh Island. The method used was experimental fishing, namely by conducting fishing operations directly in the demersal fishing area. The study showed that the fish catch consisted of five families and sixteen species of demersal fish with a total of 173 fish with an overall weight of 171.2 kg. Catches based on line size showed: line number 5 caught 24 fish weighing 47.1 kg, line number 6 caught 39 fish weighing 59.5 kg, line number 7 caught 50 fish weighing 33 kg, and line number 8 caught 60 fish weighing 31.6 kg. Data analysis tests showed that line size significantly affected the total weight of the catch (Fcount = 3.36 > Ftable = 2.96), meaning that variations in line sizes 5, 6, 7, and 8 had an effect on catch, with line number 6 providing the heaviest catch compared to other sizes.